Application of Misoprostol as a Treatment of Unexplained Infertility in Mares - Alvarenga, Marco A. [UNESP]; Segabinazzi, Lorenzo G. [UNESP] (Elsevier, 2018)
Misoprostol is a synthetic Prostaglandin E1 (PGE1), one of the prostaglandin E (PGE) family hormones, which promotes oviduct dilatation and motility, reestablishing fertility rates in mares suspected of uterine tubal block. It is known that topical application of PGE on the surface of the uterine tubes via laparoscopic procedure improved embryo recovery and pregnancy rates in barren mares with unexplained infertility. The aim of this study was to observe if the treatment using Misoprostol could be performed via intrauterine application. Mares used in this study had been barren for at least 2 years before the treatment, without embryo or pregnancy, with a history of unexplained infertility. Thus, 22 subfertile mares, aged 5 to 26 years, were treated by a deep uterine horn application, using one Cytotec tablet (200 mcg of Misoprostol, Pfizer, USA) diluted in 3 mL of sterile water, in each horn, aiming the application as close as possible to the papilla of uterine tubes. These procedures were performed during the diestrus period, and mares were bred in the next cycle. Embryos were produced, or a pregnancy was obtained from 15 of the 22 mares within the first two cycles following Cytotec treatment. Ten of 15 mares bred as embryo donors produced embryos (0.4 embryos/cycle) in the three subsequent cycles, and six of seven mares bred to carry became pregnant after treatment. In conclusion, Misoprostol therapy can be performed via intrauterine as a potential treatment for mares with unexplained infertility, making easier and safer the treatment of these mares.
Keywords: Equine; Fertility; PGE; Uterine tube